STRENGTHENING THE CONCEPT OF GENDER FROM RESEARCH ON SEXUAL DIVISION OF FISHERMEN COMMUNITY (For Development of PIPS Study Program) - Nuriza Dora; Rora Rizky Wandini; Lailatun Nur Kamalia (Jurnal Ilmiah Teunuleh, 2020)
This paper seeks to describe how fisherwomen or fishermen's wives in Percut Village decide to take up work as shell seekers as a strategy in meeting household financial needs. The method used is descriptive qualitative research to explain the financial problems faced by women in Percut Village and how they face their life problems. The data collection technique was carried out by observation, participatory observation and interviews. The results of the research show that the decline in fishermen's income causes emotional and psychological pressure for fishermen's wives to meet household needs so that they seek alternative jobs as shellfish seekers without neglecting the position of women with the main task of managing the household. There are several obstacles and challenges faced especially in childcare but they must find strategies to overcome them.